The Use of Technology in Teaching and Learning Process During the Covid-19 Pandemic - Fijanah, Mahdiana Syahri; Safitri, Ninda Rizqi; Lestari, Ika Wahyuni (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
The impact of the covid pandemic 19 that emerged recently forced the education system in Indonesia to improve its quality. One way to improve the quality of education is by utilizing information and communication technology to help teachers and students in teaching and learning. This qualitative study aims to determine teacher perceptions of the use of technology in teaching and learning activities. Data were collected using interview and the participants of this study are five teachers in Yogyakarta. Based on research conducted by researchers, the results obtained are several teachers viewed that technology is very helpful in the teaching and learning. However, some deficiencies in the use of technology in the teaching and learning process are also still found.